Influence of Achievement Motivation and Locus of Control Towards Competence of Lecturer Performance in AKUBANK ICM Cantrika Mitra Medan - Nur Aisyah (Universitas Medan Area, 2021)
This research discussed about lecturer competence in Akubank ICM Cantrika Mitra Medan of knowledge to develop increase the competence, namely by increasing education and training for lecturers who are still considered less competence. This study used quantitative methods, with questionnaires over 50 population. The Lecturer's performance is influenced by a number of factors, including (1) internal factors and (2) external factors. From the data found, motivation and locus of control tend to be